MENINGKATAN KETERAMPILAN SISWA PADA PENGURANGAN BILANGAN CACAH DENGAN TEKNIK MEMINJAM MELALUI MEDIA KANTONG BILANGAN DI KELAS II SDN PAUWO KECAMATAN KABILA KABUPATEN BONE BOLANGO - Martianty Nalole (Jurnal Inovasi, 2011)
Lowing the students skill in the class-2, caused such as not optimum usage media conerete specially media pocket quantity, teacher more to dominate process learning and lowing not able to invade the students attention to learn. Students aften fell boring cause not excessive to baudage during learning process. Actually students ability in decrease fraction need to hare by each students class-2 elementary school, because with to master that skill will make to easy for students finished their test decrease fraction with borrow technique and with to mediqa paket number hopely get to invalid activity and students participant, and to nurture the students skill to make to do as active and independent. The aim of this research is for improving the students skill in decrease fraction with technique borrow through media pocket quantity in class-2 elementary school Pauwo, Bone Bolango regency.